Implementasi Strategi Penanganan Pembiayaan Bermasalah di Bank Panin Dubai Syariah Surabaya - Sofyanto, Dita Putri; Fayakun, Aldo Deva; Ilham, Muhamad Arifin; Pratikto, Muhammad Iqbal Surya (JIOSE: Journal of Indonesian Sharia Economics, 2024)
This study examines how the strategy for handling non-performing financing at Bank Panin Dubai Syariah KCU Surabaya. The analysis method used is qualitative descriptive using a case study approach. Data collection techniques include observation and interviews. The results of the study show that in handling problematic financing, there are two divisions involved in rescue and settlement efforts for customers who experience payment problems. The Business Division (front end) is responsible for rescuing customers who are experiencing payment problems with a delay of less than 90 days by offering strategies such as installment repayment, rescheduling, reconditioning, and restructuring. Meanwhile, if the customer is late in paying more than 90 days from the due date, the handling of the customer will be taken over by the Special Asset Management Division (back end) by taking actions such as total repayment, voluntary surrender, and auction.